Influence of gender on coronary atherosclerosis and inflammatory biomarker profile: a CT angiographic study. (3rd October 2022) - Bittner, D; Roesner, C; Goeller, M; Raaz-Schrauder, D; Dey, D; Kilian, T; Achenbach, S; Marwan, M
Abstract: Background and aims: The burden of coronary atherosclerosis differs between men and women. Beyond traditional cardiovascular risk factors, inflammatory biomarkers can influence plaque formation and progression. We analyzed the influence of gender difference on coronary atherosclerosis and inflammatory cytokines. Methods: Coronary CT-Angiography was performed in 301 patients and plaque morphology was quantitatively and qualitatively assessed using semi-automated software (Autoplaque version 2.5, Cedars-Sinai Medical Center, Los Angeles, CA). We analyzed total (TPV), non-calcified (NCPV), calcified (CPV) and low-density plaque volume in mm 3 (LDPV, defined as plaque attenuation <30HU). Serum was analyzed for various cytokines including Interleukin (IL)-1a, IL-1b, IL-2, IL-4, IL-6, IL-7, IL-8, IL-10, IL-13, Il-15, IL-17, TNF-a, IFNg, CRP, MCP-1, MIP-1a, Eotaxin, G_CSF and GM-CSF using Luminex assay. Results: Out of 301 patients, 94 (31%) were female and 207 (69%) were male. As compared to women, men were significantly younger (62 vs. 57 years, p<0.001) and showed a higher BMI (28 vs. 26 kg/m 2, p=0.005). No differences were seen for hypertension, hyperlipidemia, diabetes, smoking habits and family history of CAD. All plaque characteristics showed significant higher values in men as compared to women (all p<0.05). In men, cytokine profile showed significantly lower serum levels for IL-2 (3.20 [3.20; 7.01] vs. 4.31 [3.20; 9.68]; p=0.01) and Interferon-gamma (3.20 [3.20; 14.72] vs. 8.76 [3.20; 26.26]; p<0.001) and significantly higher levels for MCP-1 (224 [117; 327] vs. 155 [49; 260]; p<0.001). In multivariable logistic regression analysis, Interferon-gamma showed significant inverse association to male gender (OR 0.35; 95% CI: 0.17–0.72; p=0.004), but IL-2 and MCP-1 did not. The association of Interferon-gamma to gender was independent of age (OR 0.57; 95% CI: 0.43–0.76; p<0.001) and BMI (OR 2.12; 95% CI 1.25–3.62; p=0.006) Conclusion: Coronary plaque volume and morphology significantly differs between men and women and so does the inflammatory cytokine profile. Albeit significantly lower coronary plaque burden in women, serum levels of interferon-gamma - a known pro-inflammatory cytokine - was significantly higher in women with independent association to gender. Whether interferon-gamma plays contradicting roles in the process of coronary atherosclerosis in men and women needs to be explored in future studies to identify potential gender-specific targets for therapeutic interventions. Funding Acknowledgement: Type of funding sources: None.